THE INFLUENCE OF POSSESSIVE BRAND NAMES ON CONSUMER DECISIONS AND PREFERENCES: AN EXPLORATION OF THE ROLE OF PERCEIVED CONTROL - Zaenal Aripin; Ucu Supriatna; M. Syafarudin Mahaputra (PT. Kreatif Indonesia Satu, 2024)
The use of possessive brand names has become an important strategy in marketing efforts to strengthen brand identity, attract consumer attention, and differentiate the brand from competitors. However, little research has paid attention to the role of perceived control by consumers in the relationship between brand name possessiveness and consumer preferences. Therefore, this study aims to explore in depth the influence of possessive brand names on consumer decisions and preferences, considering the role of perceived control in these dynamics. This research aims to explore the relationship between possessive brand name use, perceived control by consumers, and consumer preferences for brands. We wanted to understand how the use of possessive brand names influences consumers' perceptions of control and ownership, and how it influences their preferences for certain brands. This research uses the Systematic Literature Review (SLR) research method which allows a thorough exploration of the influence of possessive brand names on consumer decisions and preferences, as well as the role of perceived control in this context. By conducting SLR, this research will compile and analyze various empirical, theoretical and conceptual research relevant to this topic. Data analysis shows a significant relationship between possessive brand name use and perceived control by consumers. The use of a possessive brand name tends to increase the perception of control exerted by the brand over a particular product or service. Additionally, it was found that consumers' perceived control influenced their preference for the brand. Consumers tend to prefer brands that provide a sense of control or ownership.